Wireless multichannel hybrid data acquisition system for functional rehabilitation of paralyzed limbs - LUO Zhicheng; TIAN Ning; YANG Guang; QIN Feizhou; BAO Xueliang (物联网学报)
A wireless multi-channel hybrid data acquisition system was presented, consisting of two distinct components: a hardware system and a PC data acquisition analysis and processing software system. The hardware system was set with the number of surface electromyography (sEMG) signal acquisition channels and the number of inertial measurement unit (IMU) according to the target requirements by pressing a key, and sEMG signal transmission tasks and kinematics data acquisition tasks corresponding to the number of IMUs were created based on the FreeRTOS operating system, and the mutually exclusive signal volume technique was used to ensure that the data acquired by each task were transmitted to the PC software system via Wi-Fi. The data acquisition tasks were created based on the FreeRTOS operating system, and the kinematics tasks corresponding to the number of IMU sensors were created, and the mutually exclusive signal volume technique was used to ensure that the data acquired by each task was transmitted to the PC software system via Wi-Fi. The designed hybrid data acquisition system is more practical and scalable in the field of motor function rehabilitation for paralyzed limbs compared to the current commercial Trigno wireless based mixed signal acquisition system and other self-developed systems.